2011
DOI: 10.2169/internalmedicine.50.4634
|View full text |Cite
|
Sign up to set email alerts
|

Primary Gastric Tuberculosis Presenting as Non-Healing Ulcer and Mimicking Crohn's Disease

Abstract: A 39-year-old woman was referred to our hospital for treatment of a non-healing gastric ulcer. Esophagogastroduodenoscopy (EGD) revealed an erosion in the pyloric antrum and a longitudinal ulcer on the lesser curvature of the gastric body. The histopathologic examination of biopsy specimens revealed noncaseating epithelioid granulomas. Acid-fast staining did not reveal bacilli. The differential diagnosis included gastric tuberculosis, Crohn's disease, and sarcoidosis and empiric antituberculous therapy consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…However, even if a pathological biopsy is performed under a gastroscope, the pathological result of lesions may be non-speci c in ammation [14]. Ishii et al once reported that patients with primary gastric tuberculosis showed negative acid-fast bacilli staining but were effective for empirical ATT [15]. Tuberculous granuloma is more likely to produce negative results, which may be related to the deeper location of tuberculous granuloma [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, even if a pathological biopsy is performed under a gastroscope, the pathological result of lesions may be non-speci c in ammation [14]. Ishii et al once reported that patients with primary gastric tuberculosis showed negative acid-fast bacilli staining but were effective for empirical ATT [15]. Tuberculous granuloma is more likely to produce negative results, which may be related to the deeper location of tuberculous granuloma [16].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our patient showed negative acid-fast bacilli staining. Ishii et al have demonstrated a patient with primary gastric TB showing negative acid-fast bacilli staining, but the patient responded to empiric ATT effectively [9]. Baylan et al have also shown that a patients presented negative acid-fast bacilli staining and negative bacterial culture of the biopsy specimen, whereas had positive PCR for M. TB [20].…”
Section: Discussionmentioning
confidence: 99%
“…Two cases were gastric TB with concomitant cancer [18, 24]. PCR was commonly used to diagnose gastric TB since 2011 (Table 1) [8, 9, 1518]. Most cases presented caseating granuloma in endoscopic biopsy specimens or surgical specimens (Table 1).…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The presentation of these patients varies. Patients may present with haematemesis, 4 non-healing chronic ulcer 5 , mimicking malignancy 6 , gastric perforation 7 and gastric outlet obstruction. 8 Primary isolated gastric TB in absence of pulmonary TB in immune competent host is rare.…”
Section: Introductionmentioning
confidence: 99%